STRATEGI USAHA KECIL DAN MENENGAH (UKM) BERBASIS EKONOMI KREATIF PENGOLAHAN KOPI KABUPATEN ACEH TENGAH - Abdul Azizs; Rosdaniah Rosdaniah (ITB AAS INDONESIA Surakarta, 2021)
Coffee processing carried out by the people of Central Aceh is part of an activity that can increase the income of coffee farmers. This activity is the role of Small and Medium Enterprises (UKM), because the existing coffee processing is people's coffee processing, the community is the actors who are members of community plantations. SMEs market their coffee through social media and creative business actors, the aim of which is to get buyers widely. In the midst of the current era of globalization, people have used social media a lot as a means of promotion and information, the aim of which is to bring their production closer to consumers.